Proceedings of the 32nd International Symposium on Lattice Field Theory — PoS(LATTICE2014) 2015
DOI: 10.22323/1.214.0128
|View full text |Cite
|
Sign up to set email alerts
|

The leading disconnected contribution to the anomalous magnetic moment of the muon

Abstract: The hadronic vacuum polarization can be determined from the vector correlator in a mixed timemomentum representation. We explicitly calculate the disconnected contribution to the vector correlator, both in the N f = 2 theory and with an additional quenched strange quark, using non-perturbatively O(a)-improved Wilson fermions. All-to-all propagators are computed using stochastic sources and a generalized hopping parameter expansion. Combining the result with the dominant connected contribution, we are able to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This concerns both a hvp µ , studied in [28][29][30][31][32][33][34][35][36][37][38][39][40], as well as a hlbl µ [41][42][43][44][45][46][47][48][49]. Lattice calculations of a hvp µ proceed by evaluating a convolution integral over Euclidean momenta Q 2 [28,50].…”
Section: Jhep10(2017)020mentioning
confidence: 99%
See 1 more Smart Citation
“…This concerns both a hvp µ , studied in [28][29][30][31][32][33][34][35][36][37][38][39][40], as well as a hlbl µ [41][42][43][44][45][46][47][48][49]. Lattice calculations of a hvp µ proceed by evaluating a convolution integral over Euclidean momenta Q 2 [28,50].…”
Section: Jhep10(2017)020mentioning
confidence: 99%
“…Statistically accurate results for quantities such as ∆ f require "all-to-all" propagators which are commonly computed using stochastic noise sources. In [35] it was shown that the statistical accuracy of G disc (x 0 ) can be significantly enhanced when ∆ ud and ∆ s are computed using the same random noise vectors, since the correlations between the light and strange quark contributions largely cancel the stochastic noise.…”
Section: Determination Of the Quark-disconnected Contributionmentioning
confidence: 99%
“…Recently, for example, the full set of quark-disconnected contributions, so far believed to be the main obstacle in obtaining a lattice determination of a (2)had µ at the percent level, has been computed with much improved precision in lattice QCD with physical light quark masses [17]. The crucial step in this computation was identifying the dynamics mainly responsible for the disconnected contribution and tailoring corresponding lattice techniques [17,22].…”
Section: Contentsmentioning
confidence: 99%
“…The fit, using a time range from 3 to 40 is stable from 6 exponentials upwards with a χ 2 /dof = 1.1 (Q=0.2). It gives am ω = 0.1537 (10) and am φ = 0.1775 (7). am ω is somewhat lower than the value (0.1568(4)) obtained by the Hadron Spectum collaboration which included mixing between light and strange bilinears using more operators and the generalised eigenvalue fit method [24].…”
Section: Lattice Resultsmentioning
confidence: 99%
“…Calculations of the disconnected contribution to a μ;HVP have concentrated on stochastic determinations using various noise-reduction methods and several calculations are underway, see, for example Ref. [10].…”
Section: Introductionmentioning
confidence: 99%